Biodegradation of phenol in batch and continuous flow microbial fuel cells with rod and granular graphite electrodes. Issue 2 (17th January 2018) - Moreno, Lyman; Nemati, Mehdi; Predicala, Bernardo
ABSTRACT: Phenol biodegradation was evaluated in batch and continuous flow microbial fuel cells (MFCs). In batch-operated MFCs, biodegradation of 100–1000 mg L −1 phenol was four to six times faster when graphite granules were used instead of rods (3.5–4.8 mg L −1  h −1 vs 0.5–0.9 mg L −1  h −1 ). Similarly maximum phenol biodegradation rates in continuous MFCs with granular and single-rod electrodes were 11.5 and 0.8 mg L −1  h −1, respectively. This superior performance was also evident in terms of electrochemical outputs, whereby continuous flow MFCs with granular graphite electrodes achieved maximum current and power densities (3444.4 mA m −3 and 777.8 mW m −3 ) that were markedly higher than those with single-rod electrodes (37.3 mA m −3 and 0.8 mW m −3 ). Addition of neutral red enhanced the electrochemical outputs to 5714.3 mA m −3 and 1428.6 mW m −3 . Using the data generated in the continuous flow MFC, biokinetic parameters including μ m, K S, Y and K e were determined as 0.03 h −1, 24.2 mg L −1, 0.25 mg cell (mg phenol) −1 and 3.7 × 10 −4  h −1, respectively. Access to detailed kinetic information generated in MFC environmental conditions is critical in the design, operation and control of large-scale treatment systems utilizing MFC technology.